Exploration and Practical Research on the Path of Rural Revitalization Driven by New Quality Productivity - Xu, Heyun (Journal of Global Economy, Business and Finance, 2025)
Implementing the rural revitalization strategy is an important foundation for building a modern economic system. New quality productivity, as an advanced form of productivity characterized by high technology, high efficiency, and high quality, has extraordinary significance in driving rural revitalization, mainly reflected in multiple dimensions such as economy, society, ecology, and culture. This article focuses on how new quality productivity drives rural revitalization, explores the challenges faced by current rural revitalization, and proposes practical paths such as strengthening digital infrastructure construction, enhancing talent support, and expanding financing channels to promote rural industrial upgrading and common prosperity for farmers.